2015
DOI: 10.1186/s12872-015-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

The duration of balloon inflation affects the luminal diameter of coronary segments after bioresorbable vascular scaffolds deployment

Abstract: BackgroundAdequate expansion is critical to achieve optimal Bioresorbable Vascular Scaffolds (BVS) apposition to the vessel wall. However, compared to metallic stents, BVS present different mechanical properties. Hence, slow deployment and maintenance of balloon inflation for at least 30” is recommended for BVS implantation. However, since no evidences are available demonstrating the superiority of a longer balloon dilatation time, the implantation technique is highly variable among different centers.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“… 52) Target pressure should be maintained for at least 30 seconds, because a significant larger lumen diameter is obtained with a longer inflation time. 53) …”
Section: Indications For Brs Implantationmentioning
confidence: 99%
“… 52) Target pressure should be maintained for at least 30 seconds, because a significant larger lumen diameter is obtained with a longer inflation time. 53) …”
Section: Indications For Brs Implantationmentioning
confidence: 99%
“…Thus, the persistent application of a constant inflation pressure until pressure stabilization develops may be a safe and effective approach to fully expand these devices. As with metallic stents, a recent study has shown improved stent expansion with a 30 s duration inflation compared to a rapid inflation/deflation sequence . POP may be attractive with this stent type since lesion and stent characteristics would guide the duration of inflation rather than an arbitrary time.…”
Section: Discussionmentioning
confidence: 99%
“…The PSP technique is distinctively beneficial in the case of aggravated risk of thrombosis, e.g., in diabetic patients [124,138]. In line with this concept, the use of a longer inflation time, as suggested by the producer, allows better for device expansion and a more homogeneous apposition [53]. In order to select the proper size of BVS, the measurement of the target's diameter was observed to be equally accurate under the guidance of either angiography or OCT [139].…”
Section: Niche For Bvs and Optimization Of Bvs Actionmentioning
confidence: 96%
“…In order to obtain the appropriate mechanical framework of these stents, it became necessary to increase the thickness of the strut, because of lower tensile strength, reduced stiffness and the chance of deformation [35,52]. Studies have shown that in order to avoid strut rupture or abnormal decomposition, ABSORB stents require accurate lesion, judicious patient selection and an appropriate implantation technique, as they are able to stretch up to 0.7 mm beyond the nominal diameter [36,53]. ABSORB stents are radiolucent and therefore may not be visualized in fluoroscopy.…”
Section: Overview Of First and Second Generation Bvsmentioning
confidence: 99%
See 1 more Smart Citation